Analysis Of Women’s Representation In Carrying Out Legislative Functions As Members Of The Boyolali Regency Regional House Of Representatives - Arina Nur Azizah; Nanik Sutarni; Adhiputro Pangarso Wicaksono (Penerbit Hellow Pustaka, 2025)
The lack of support for women remains one of the obstacles to achieving the 30% quota for female representation in legislative institutions. This lack of support significantly affects the performance of female legislators in parliament. In the Boyolali Regency DPRD for the 2024–2029 period, out of 50 legislative members, only 13 are women—around 26%—falling short of the ideal representation target. This condition reflects the continued underrepresentation of women in parliament, despite the fact that electoral and political party laws in Indonesia have provided opportunities for women to engage in politics and legislative membership. This study aims to examine how female legislators carry out their legislative functions in the Boyolali Regency DPRD, while also identifying the challenges they face and the strategies they adopt. The research is grounded in Hanna Pitkin’s theory of Women Representation, which distinguishes between descriptive and substantive representation. A qualitative descriptive approach was employed, with data collected through interviews, observation, and documentation. The results indicate that although the quantitative representation of women remains low, female members of the Boyolali DPRD have actively participated in all stages of the legislative process—from drafting and deliberation to ratification of local regulations. Challenges encountered include the burden of proving competence in a male-dominated political culture, balancing domestic and public roles, aspirational pressures from constituents, and moral responsibility in promoting gender-related issues. Strategies undertaken include strengthening formal legitimacy through legal frameworks, initiating pro-women regulations, improving communication in legislative forums, reinforcing constituent connections, and demonstrating tangible performance outcomes. These findings suggest that the involvement of women in legislative functions goes beyond fulfilling numerical representation; it also contributes to more inclusive and gender-sensitive policymaking. Therefore, enhancing the capacity and expanding the political space for women is essential for building a representative and just parliament.